Effectiveness and Efficiency of Using LINAC Precise and Cobalt-60 Medical Devices at Dr. Mohammad Hoesin Hospital Palembang - Widyastuti, Aulia; Masdahlena (RSUP Dr Moh Hoesin Palembang, 2022)
Hospitals are social institutions that provide quality health services to every customer. To meet expected service standards, hospitals should have effective procurement of medical equipment. This study aims to evaluate the effectiveness and efficiency of utilities in the use of medical devices in supporting services at RSUP Dr. Mohammad Hoesin Palembang, with descriptive analytical research using quantitative methods with a cross sectional research design. The research results show that there is a significant difference between the Break Event Point (BEP) value before and after purchasing the Cobalt 60 aircraft from the target of 90 patients per day to 87 patients per day, and there is a significant difference between the BEP value before and after purchasing the Precise LINAC aircraft from the target of 70 patients per day to 55 patients per day. Based on the calculation of the effectiveness and efficiency of the utility of using the Cobalt 60 and Linac Precise aircraft, it can be concluded that the utility of using the Cobalt 60 aircraft at RSUP Dr. Mohammad Hoesin Hospital Palembang is considered ineffective (50%) but efficient (70.88%) with a BEP value of 5.5 years; while the utility of using the Linac Precise aircraft at RSUP Dr. Mohammad Hoesin Hospital Palembang is considered effective (113%) and efficient (51.77%) with a BEP value of 4.1 years. The data above shows that hospitals experienced slight losses due to the Covid-19 pandemic because the number of patients using medical equipment did not reach the target, but hospitals were able to manage expenditure well so that there was a decrease in the efficiency ratio every year in the procurement of medical equipment.